Keseimbangan Model Pengelolaan Dana Desa untuk Meningkatkan Kesejahteraan Masyarakat Pesisir Kabupaten Bonebolango - M Mattoasi; Candra Cuga; Muhammad Sarlin; S Sudirman (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2021)
Village funds distributed to every village, especially in Bone Bolango District, are for development purposes and community empowerment. This study aims to determine the balance model of village fund management through Village-Owned Enterprises (Kemendes PDTT, 2019). The research method used is a mixed-method (mix-method) by recording quantitative data and qualitative data through in-depth interviews for any information given to village heads and village officials in Bone Bolango District, Gorontalo Province. The results showed that community involvement in creating balance is fundamental to realizing a prosperous society. Although, on the other hand, the problem of managing village funds is that they are not maximally used to incubate poverty, have not been on target, or have not matched the potential of the village; the focus of development is still oriented towards infrastructure, which is still found in the field.